Advanced Endoscopy Trainee Involvement Early in EUS Training May Be Associated with an Increased Risk of Adverse Events. Issue 2 (12th December 2018) - Khan, Usman; Abunassar, Michael; Chatterjee, Avijit; James, Paul D
Abstract: Background: The quality of endoscopic ultrasound (EUS) involving advanced endoscopy trainees (AETs) is not well understood. In this study, we aimed to examine adverse events (AE) risk and diagnostic yield of EUS procedures involving AETs. Methods: We conducted a retrospective single-centre review from September 2009 to August 2015. Clinical, procedural, cytological, and hospital visit data within 30 days of the EUS procedure was collected. Primary outcomes were occurrence of an AE and a diagnostic specimen on cytopathology. Each AE was classified as "definitely related, " "possibly related, " or "not related " to the EUS procedure based on a previously defined consensus approach. Advanced endoscopy trainee involvement was established through the operative report. Results: Our study included 1657 EUS procedures, of which 27% (451 of 1657) involved AETs. Endoscopic ultrasound was most commonly performed to evaluate pancreatic pathology (46% of cases). Overall AE incidence was 3.4%; it was 4.9% when an AET was involved and 2.8% when the EUS was performed without an AET ( P = 0.04). The risk of an AE when AETs were involved was greatest in the first three months of training (7.9% versus 2.7%, P = 0.04). Multivariate analysis limited to the first three months of training demonstrated AET involvement to be associated with an increased AE risk after adjusting for patient and procedural factors (adjusted OR 3.2; 95% CI, 1.1–8.7; P = 0.03). The overall diagnostic yield was 76%. This was not compromised by AET involvement for any quartile of training. Conclusions: We observed an increased risk of EUS-related AEs when procedures involved AETs during the first three months of training.